2017
DOI: 10.1088/1361-6560/aa56b6
|View full text |Cite
|
Sign up to set email alerts
|

Fast approximate delivery of fluence maps for IMRT and VMAT

Abstract: In this article we provide a method to generate the trade-off between delivery time and fluence map matching quality for volumetric modulated arc therapy (VMAT). At the heart of our method lies a mathematical programming model that, for a given duration of delivery, optimizes leaf trajectories and dose rates such that the desired fluence map is reproduced as well as possible. This model was presented for the single map case in a companion paper (Craft and Balvert). The resulting large-scale, non-convex optimiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…Note that pure sliding window delivery is not necessarily the most efficient algorithm for dynamic fluence map delivery . However, it results in a simple equation which estimates the time to deliver a fluence map.…”
Section: Methodsmentioning
confidence: 99%
“…Note that pure sliding window delivery is not necessarily the most efficient algorithm for dynamic fluence map delivery . However, it results in a simple equation which estimates the time to deliver a fluence map.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, there is a potential to improve the dosimetric quality of a treatment plan by utilizing an additional photon energy beam as an extra degree of freedom through simultaneous optimization process. To our knowledge, this notion has not been reported in any of the previous literatures for VMAT treatment planning.…”
Section: Introductionmentioning
confidence: 70%
“…A beam segment length of 10° was selected in the first step based on previously published results, which demonstrated that in order to achieve a high‐quality plan the gantry angles should be spaced evenly ≤10° . Current clinical photon beam energies in radiotherapy planning mostly range from 6 to 18 MV.…”
Section: Discussionmentioning
confidence: 99%
“…To that end, we adopt the approach used in Ref. and define a PWL function Hj:false[0,wfalse]false[0,1false] of the form Hjfalse(xfalse)=00xj1xj+1j1<xj1j<xw as shown in Fig. .…”
Section: Methodsmentioning
confidence: 99%
“…However, this gives rise to a far more challenging LS problem, which requires the development of new models and efficient solution methods. Craft and Balvert have recently studied the potential benefit of bidirectional leaf trajectories for IMRT and VMAT . In particular, they formulate the LS problem for each MLC row as a nonconvex optimization problem in terms of the left‐ and right‐leaf trajectories and use standard gradient‐descent methods to solve the formulation.…”
Section: Introductionmentioning
confidence: 99%